Follow me stories from the Bible - Pihl, Herman Gottfrid 1894-; Beckman, Karin 1904-. (London Adam & Charles Black, 1966)
Biblical legends retold in prayers, poems, and stories.
Keywords: Bible stories, English; Bible stories; Children -- Prayer-books and devotions; Prayer books and devotions